PENGARUH PROFITABILITAS, CAPITAL INTENSITY DAN LEVERAGE TERHADAP TAX AVOIDANCE - Ajron Ahima Muh; Yohanes (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This study aims to obtain empirical evidence regarding the effect of profitability, capital intensity, leverage, company size, audit quality, company age, and sales growth on tax avoidance proxied by Current Effective Tax Rate (CETR). The population of this study amounted to 182 manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2021. The method for data collection uses purposive sampling. The research sample amounted to 80 companies consisting of 240 data. Statistical testing in this study used multiple regression analysis methods. This study proves that profitability, leverage, company size, and audit quality affect tax avoidance. Meanwhile, capital intensity, company age, and sales growth do not affect tax avoidance. High profitability will affect the tax burden, and the company will practice tax avoidance. The company has high leverage, so the interest rates on intensive tax are getting smaller, and the company will not practice tax avoidance. The company has a large company size, so it will make good plans to practice tax avoidance. KAP audited the company The Big Four will be more thorough and detailed about the company's financial statements.